2017
DOI: 10.1093/fampra/cmx090
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for care of osteoarthritis in primary care settings: a systematic literature review

Abstract: BackgroundDespite the high prevalence of osteoarthritis and the prominence of primary care in managing this condition, there is no systematic summary of quality indicators applicable for osteoarthritis care in primary care settings.ObjectivesThis systematic review aimed to identify evidence-based quality indicators for monitoring, evaluating and improving the quality of care for adults with osteoarthritis in primary care settings.MethodsOvid MEDLINE and Ovid EMBASE databases and grey literature, including rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Previously published reviews 20 21 34 35 59 60 focused on QIs specific healthcare settings (eg, primary care and centralised intake care systems), or perspectives (eg, patients’ perspectives). To our knowledge, this is the first systematic review that provides a comprehensive overview of QIs for KHOA outlining the differences and similarities between healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published reviews 20 21 34 35 59 60 focused on QIs specific healthcare settings (eg, primary care and centralised intake care systems), or perspectives (eg, patients’ perspectives). To our knowledge, this is the first systematic review that provides a comprehensive overview of QIs for KHOA outlining the differences and similarities between healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have focused on QIs for OA in primary care. 20 21 However, an overview of QIs that take into account the differences in healthcare settings and countries is lacking. Such an overview will support healthcare providers and policy makers in selecting the contextually appropriate QIs.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…First, systematic reviews were conducted to identify a set of evidence-based and valid quality indicators for assessing care for older adults in ambulatory care settings by each disease category, including diabetes, major depression, hypertension, chronic ischemic heart disease and osteoarthritis, as well as selected disease combinations [17, 18]. The resulting indicators were then sorted into those potentially measurable with the Ontario administrative data, and those that required other sources of data.…”
Section: Methodsmentioning
confidence: 99%
“…There are few published indicators for care for older adults with diabetes that specifically address comorbidity with concordant conditions, including hypertension and chronic ischemic heart disease [1416]. Moreover, there are no indicators identified for care for older adults with diabetes with comorbid discordant conditions, including osteoarthritis and major depression [17, 18]. The present study addresses these gaps and aimed to: 1) critically appraise and select the most appropriate set of quality indicators for ambulatory care for older adults with five selected disease combinations that are amenable to measurement using administrative data, using a Delphi technique, including: a) concordant conditions: diabetes with comorbid hypertension and ischemic heart disease, b) discordant conditions: diabetes with comorbid osteoarthritis and depression, c) both types: diabetes with comorbid hypertension and osteoarthritis, and 2) prepare a summary of defined quality indicators by each selected disease combination.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the quality of health care for patients with knee OA, a Belgian set of 21 process QIs, based on international evidence‐based guidelines, was developed by a multidisciplinary expert panel (9). Even though OA is one of the most prevalent conditions in general practice, evidence‐based and valid QIs for assessing the quality of primary care for knee OA are scarce (10). However, numerous studies have shown that high performance on process QIs does not consequently lead to the desired patient health outcomes (11,12).…”
Section: Introductionmentioning
confidence: 99%